2010
DOI: 10.1186/1742-6405-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Multi-analyte profiling of ten cytokines in South African HIV-infected patients with Immune Reconstitution Inflammatory Syndrome (IRIS)

Abstract: BackgroundImmune reconstitution inflammatory syndrome (IRIS) is an important complication of HAART in sub-Saharan Africa, where opportunistic infections (OIs) including mycobacteria and cryptococcus are common. The immune system's role in HIV infected patients is complex with cytokine expression strongly influencing HIV infection and replication.MethodsWe determined the expression patterns of 10 cytokines by Luminex multi-analyte profiling in 17 IRIS nested case-control pairs participating in a prospective Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…These authors also showed IL-10 to be correlated to viral load. In another South African-based study INF-g, IL-6 and IL-10 were elevated in a group of HIV-infected individuals with immune reconstitution inflammatory syndrome [16]. IL-2 and IL-6 were key cytokines elevated in simian immunodeficiency virus-infected monkeys with encephalitis [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also showed IL-10 to be correlated to viral load. In another South African-based study INF-g, IL-6 and IL-10 were elevated in a group of HIV-infected individuals with immune reconstitution inflammatory syndrome [16]. IL-2 and IL-6 were key cytokines elevated in simian immunodeficiency virus-infected monkeys with encephalitis [12].…”
Section: Resultsmentioning
confidence: 99%
“…Measuring cytokine alterations during HIV infection [11][12][13][14][15][16] and other pathological states [17][18][19][20][21] is increasingly being investigated for use in predicting disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…These results can also be linked to anti-HIV properties of this plant; low levels of IL-17A in HIV-1 infection is associated with non-progression (Yue et al, 2008). IL-17A along with other cytokines such as IL-2 and IL-6 are elevated during the different stages of HIV infection (Keating et al, 2011;Nixon and Landay, 2010;Worsley et al, 2010;Yue et al, 2008). Therefore lowering the production of this cytokines especially IL-17A could contribute to slow or nonprogression of HIV infection.…”
Section: P Barbatus Inhibits Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…It is unclear why some patients are more likely than others to develop IRIS during immune reconstitution. Several studies of immunologic profiling have shown that IRIS patients had greater numbers of activated CD4+ T cells of the effector memory subtype 45 with increased expression of interferon-+ 46 and programmed-death molecule 1 (PD-1) prior to ART initiation, suggesting that they are primed for immune activation. 47 While PD-1 expression has been linked to failure of immune restoration in ART and T-cell exhaustion, 47 its presence in patients with IRIS may imply a disordered process of immune restoration.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%